An assessment of metal pollution in surface sediments of Seyhan dam by using enrichment factor, geoaccumulation index and statistical analyses - Çevik F.; Göksu M.Z.L.; Derici O.B.; Ö, Findik (Springer Science and Business Media LLC, 2008)
The aim of this study was to determine if high concentrations of any heavy metals exist in the sediment of Seyhan Dam reservoir to be considered toxic to the aquatic environment. Surface sediment samples from five stations in the Seyhan dam were collected quarterly from 2004 to 2005 and examined for metal content (Cr, Zn Cu, Mn, Cd, Fe, Ca, K, and Na), organic matter, and grain size. Correlation analyses showed that metal content of Seyhan dam sediment was affected by organic matter and grain size. The results have been compared with values given in the literature. The evaluation of the metal pollution status of the dam was carried out by using the enrichment factor and the geoaccumulation index. A comparison with sediment quality guideline values has also been made. Based on the enrichment factor, dam sediments were treated as a moderately severe enrichment with Cd and minor enrichment with Cr and Mn. The results of geoaccumulation index reveal that sediments of Seyhan Dam were strongly polluted in stations 1, 2, 4, and 5, and were moderately polluted in station 3 with Cd. Moreover, Cd and Cr concentrations in the sediments were above TECs except ERL for Cd.
Keywords: Geologic Sediments; Geoaccumulation index; Seyhan dam; Turkey; Metal; Mediterranean Region; Enrichment factor; Metals; Water Supply; Humans; Soil Pollutants; Sediment; Particle Size; Water Pollutants, Chemical; Environmental Monitoring; 6. Clean water; 13. Climate action